Magnetism and Néel skyrmion dynamics in GaV_{4}S_{8-y}Se_{y} - T. J. Hicken; S. J. R. Holt; K. J. A. Franke; Z. Hawkhead; A. Štefančič; M. N. Wilson; M. Gomilšek; B. M. Huddart; S. J. Clark; M. R. Lees; F. L. Pratt; S. J. Blundell; et al. (Physical Review Research, 2020)
We present an investigation of the influence of low levels of chemical substitution on the magnetic ground state and Néel skyrmion lattice (SkL) state in GaV_{4}S_{8-y}Se_{y}, where y=0,0.1,7.9, and 8. Muon-spin spectroscopy (μSR) measurements on y=0 and 0.1 materials reveal the magnetic ground state consists of microscopically coexisting incommensurate cycloidal and ferromagnetic environments, whereas chemical substitution leads to the growth of localized regions of increased spin density. μSR measurements of emergent low-frequency skyrmion dynamics show that the SkL exists under low levels of substitution at both ends of the series. Skyrmionic excitations persist to temperatures below the equilibrium SkL in substituted samples, suggesting the presence of skyrmion precursors over a wide range of temperatures.